HUBUNGAN PEER GROUP DENGAN MINUM ALKOHOL PADA ANAK REMAJA DI SEKOLAH MENENGAH PERTAMA PRABUMULIH - Aprida Manurung (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Adolescent updates or current, is a trend issue in the advancement of technology that exists today, but the current model or often called the millennial trend has reached a negative influence. Negative influences often associated with millennial trends for adolescents are smoking, drinking, drugs, until violence with other teenagers. This will have a bad impact because the younger generation is the next generation of the nation, how the future life of this nation if from a young age they are already affected by the negative impact of the trend millennial. This research aims to find out the relationship between Peer Group and alcoholic beverages. This study uses an analytical survey method with a cross sectional approach. Research location in Junior High School Prabumulih City, Sampling uses cluster random sampling technique with a population of 250 respondents and a sample of 100 respondents by paying attention to inclusion and exclusion criteria. The results showed that adolescents who had peer groups with group members amounting to 4 people or more at risk of having the habit of drinking alcoholic drinks 4 times greater than those of adolescents who had peer groups with group members 1-3 people. The statistical test results have a relationship between the peer group and drinking alcoholic beverages. Teens who have peer group of ? 4 people are more at risk of making alcohol drinking decisions a daily habit.